Influence of Spike Pretreatment at Low Temperatures on Efficiency of Spring Barley Haploid Production in Anther Culture in Vitro - Bilynska , Olena (Problems of Cryobiology and Cryomedicine, 2020)
The spike pretreatment at low temperatures before isolating and inoculating anthers in a nutrient medium is an important element of technology for producing haploids of many species of higher plants. This procedure not only extends the optimal stage duration of microspores' development, but stimulates their abnormal multiple division with formation of callus, embryoids and increases the frequency of plant regeneration. Here, we have studied the impact of the duration and the mode of spike pre-treatment, genotype and gel-forming component of nutrient medium on the efficiency of morphogenic structure formation and plant regeneration in spring barley in vitro anther cultures. The cut tillers of two varieties and lines and the isolated spikes were kept at 4ºC for 5 (the control) and 28 days, respectively. The aseptically isolated anthers were cultured in nutrient media, contained salts of macro- and microelements according to the N6 and MS formulations, physiologically active substances, maltose, and differed by gel-forming components (agar or chemically modified starch D5a-M) at the optimal concentrations for gel formation. The advantage of isolated spike pretreatment at 4°C within 28 days versus the tiller storage after a 5-day exposure and the expediency to use starch instead of agar within the nutrient medium, have been established. The combination of these methodical approaches resulted in an increase in the frequency of green plant regeneration in line DH00-126 with a genetically determined high capability to in vitro androgenesis from 23.4 up to 100%. Probl Cryobiol Cryomed 2020; 30(1): 68–76